Effects of Imagined Consumption and Simulated Eating Movements on Food Intake: Thoughts about Food Are Not Always of Advantage - Haasova, Simona; Elekes, Botond; Missbach, Benjamin; Florack, Arnd (Frontiers in Psychology, 2016)
Imagined food consumption is a method of elaborately imagining oneself eating a specific food that, when repeated 30 times, has been shown to decrease subsequent intake of the same food. The technique relies on a memory-based habituation process when behavioral and motivational responses to a stimulus decrease after its repeated presentation. Thus, repeatedly imagining food consumption leads to food-specific habituation effects. Large numbers of imagined consumption repetitions are effortful and time consuming and can be problematic when applied in interventions with the goal of reducing food intake. In the present study, we assessed the efficacy of the technique at smaller numbers of repetitions while testing motor simulation as a potential facilitator of the habituation-based consumption-reduction effect. 147 participants imagined eating chocolate pudding 15 or 3 consecutive times and simultaneously performed either facilitating or not-facilitating eating movements. Results showed that participants who imagined eating the chocolate pudding 15 times (M15 = 178.20, SD15 = 68.08) ate more of the pudding than those who imagined consuming it 3 times (M3 = 150.73, SD3 = 73.31). The nature of the motor movements that were performed did not impact this effect. The data suggest that the imagined food consumption technique can result in an unexpected increase in food consumption, when smaller numbers of imagination repetitions are performed.